ANALISIS MENGENAI DERAJAT KESABARAN MAHASISWA FIKOM UNPAD 2005 YANG BERMASALAH DALAM SKRIPSI - Lisa Widawati (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
This study aimed to describe and analyze the degree of patience among Padjajaran University Communication student class of 2005 with GPA of 2.75 minimum, is problematic when finishing thesis viewed from the perspective of Qur’an and Hadith. The concept of patient has a dimension related to the firm on the establishment, determination and perseverance which is elaborated in the indicators contained related matters which is in line with the Psychological concept, such as: in the form of behavioral consequent, consistent, endurance, fighting spirit, the existence of stress tolerance, openness to the feedback, also having an anticipatory planning. Therefore measuring instrument is constructed based on the lattice. The samples were 10 people taken in incidental population of 21 students which is still problematic in the completion of their thesis. Results showed that most of the students who studied in general in fact possess sufficient degree of patience on that level when they face various obstacles, which are supported by its firm commitment to the establishment and resilient. However, in the aspect of perseverance, they generally have very low levels. From this description it can be concluded that even if they are problematic but they are still consistent and ready to accept the consequences of all the risks in formulating thesis is accompanied by resistance to continue with his willingness to receive feedback. However, they are problematic in making a thorough planning and anticipation so that when faced with obstacles, they were not ready to handle it. These weaknesses, if it is related to the concept of psychology, are closely related to the weakness of students' ability in self-regulation when preparingtheir thesis.